2014
DOI: 10.1111/aos.12410
|View full text |Cite|
|
Sign up to set email alerts
|

Autorefraction versus subjective refraction in a radially asymmetric multifocal intraocular lens

Abstract: ABSTRACT.Purpose: To evaluate whether the automated refraction (AR) correlates with subjective manifest (MR) refraction in eyes implanted with radially asymmetric multifocal intraocular lens (IOLs). Methods: This retrospective study evaluated 52 eyes (52 patients) implanted with a radially asymmetric multifocal IOL (LS-312 MF30, Oculentis, Germany). At 3 months postoperatively, the AR and MR values were compared to determine the correlation between the sphere (S), the spherical equivalent (SE) and the astigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…A similar tendency has been found for bifocal IOLs to a greater or lesser extent and, more specifically, a stronger trend toward myopia has been observed for refractive bifocal IOLs than for diffractive ones. 4,17 As for sectorial refractive IOLs, van der Linden et al 2 and Albarr an-Diego et al 1 found a systematic shift toward more negative values for autorefraction, between 1.00 D and 1.25 D, compared with subjective refraction, with poor correlation for cylinder values. Bissen-Miyajima et al 3 reported similar issues with refractive IOLs, hypothesizing that pupil size might confound autorefraction outcomes; actually, the geometry of the lens could be the main factor causing measurement inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar tendency has been found for bifocal IOLs to a greater or lesser extent and, more specifically, a stronger trend toward myopia has been observed for refractive bifocal IOLs than for diffractive ones. 4,17 As for sectorial refractive IOLs, van der Linden et al 2 and Albarr an-Diego et al 1 found a systematic shift toward more negative values for autorefraction, between 1.00 D and 1.25 D, compared with subjective refraction, with poor correlation for cylinder values. Bissen-Miyajima et al 3 reported similar issues with refractive IOLs, hypothesizing that pupil size might confound autorefraction outcomes; actually, the geometry of the lens could be the main factor causing measurement inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several methods are available to estimate refractive error after lens extraction and IOL implantation; these include keratometry, retinoscopy, and autorefraction; however, manifest refraction is still considered the gold standard. Autorefraction's accuracy has been found to decrease in the presence of a multifocal IOL, 2,4,16 whereas retinoscopy becomes more complicated to perform with some of these lensesdsuch as refractive sectorial IOLs dbecause of the presence of two opposite retinoscopy shadows. 1 Several authors have compared objective and subjective refraction values in refractive and bifocal diffractive IOL 349 350 351 352 353 354 355 356 357 358 359 360 361 362 363 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 382 383 384 385 386 387 388 389 390 391 392 393 394 395 396 397 398 399 400 401 402 403 404 405 406 wearers; however, to our knowledge, this is the first attempt to perform such a comparison with the more complex trifocal IOLs, which have three foci (for far, intermediate, and near distances).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This finding suggests an improved agreement between autorefraction measurements and subjective refraction in keratoconic eyes following keraring implantation, such as that both techniques can then be used interchangeably. It should be noted that the autorefractor may overestimate the negative cylinder by about 1.00 D.…”
Section: Discussionmentioning
confidence: 90%
“…12 Although early versions of autorefractors were found to be similar in performance to subjective refraction, 26 the specifications and performance of the recent models, such as those used in this study, are better. [27][28][29] For instance, like the recent autorefractors, 4,7,30 the RC-5000 is a multifunctional device, because in addition to refraction, it incorporates a keratometry facility. The device acquires radius of curvature measurements in the flat and steep meridians on a 3.0 and 6.0-mm diameter field of the central cornea.…”
Section: Of Measurementsmentioning
confidence: 99%